Effect of grouting material strength on bond strength of sleeve and acoustic emission characterization of bond failure damage process. (21st March 2022) - Han, Ruiqing; Li, Shengli; Sun, Wencong
Highlights: The relationship between grouting material strength and bonding strength was revealed. A design method is proposed to avoid bond failure of the grouted sleeves. The rapid increase of the ringing count and energy could be a precursor of the bond failure. The safety zone to avoid the bond failure of the grouted sleeves was established. Abstract: The grouted sleeve connection is widely used in fabricated structures, and the bonding performance is a vital indicator to evaluate its property. Total of 24 grouted sleeves specimens were designed to study the effect of grouting material strength on bond strength of two forms of sleeves under monotonic tensile loading. The qualitative and quantitative evaluation of the bond failure damage process of the grouted sleeves was carried out relying on acoustic emission (AE) technology. Results demonstrated that the relative displacement between the rebar and grouting material was generated after the hardening stage of the tensile process. More importantly, the relationship between grouting material strength and bonding strength was revealed. Compared with Carbon steel sleeves, ductile iron sleeves exhibited better bonding properties in the tensile process. Moreover, a designing method was proposed to prevent bond failure of the ductile iron sleeves and carbon steel sleeves. The trends of AE ringing count and energy with the variation of load could better characterize the bonding failure damage process, which corresponded well to the five stages of the tensile process. The rapid increase of the ringing count and energy level could be a precursor to the occurrence of bond failure of the grouted sleeve. The safety zone to avoid the bond failure of the grouted sleeves was established based on the AE intensity analysis. The emergence of the AE signal corresponding to the bond failure should be vigilant in engineering practice.